Revealing lattice disorder, oxygen incorporation and pore formation in laser induced two-photon oxidized graphene. (March 2019) - Mendoza, Martin E.; Ferreira, Erlon H.M.; Kuznetsov, Alexei; Achete, Carlos A.; Aumanen, Jukka; Myllyperkiö, Pasi; Johansson, Andreas; Pettersson, Mika; Archanjo, Braulio S.
Abstract: Laser induced two-photon oxidation has proven to be a reliable method to pattern and control the level of oxidation of single layer graphene, which in turn allows the development of graphene-based electronic and optoelectronic devices with an all-optical method. Here we provide a full structural and chemical description of modifications of air-suspended graphene during the oxidation process. By using different laser irradiation doses, we were able to show via transmission electron microscopy, electron energy loss spectroscopy, electron diffraction and Raman spectroscopy how graphene develops from its pristine form up to a completely oxidized, porous and amorphous carbon layer. Furthermore, the gradual control of the oxidation process is used to correlate lattice disorder, oxygen incorporation and pores formation in graphene oxide. This study provides a model system that will benefit research on graphene and other two-dimensional materials. Graphical abstract: